Progress towards Millennium Development Goals with women empowerment - Chaturvedi, Shobha; Singh, Geetu; Rai, Preeti (Indian Journal of Community Health, 2016)
Background: Women empowerment is a powerful determinant of their own, children’s and their families’ health. Perhaps, due to this fact, promotion of gender equality and empowering women was kept as one of the eight Millennium Development Goals (MDGs). Objective: The present analysis was undertaken to study the effect of women empowerment on health of women, family planning and various health indicators of children. Methods: Available data from National Surveys in India, various research studies and evidences from published global studies were gathered and further analyzed. Results: Census 2011 (India) have shown that states having higher women literacy, like Tamil Nadu and Maharashtra (75%), have better positive indicators of health than states like Rajasthan with 53 % literacy. NFHS -3 (India) showed that empowered women had better access to maternal services (76 %), more use of contraception (66.6%) and resultantly, had lower neonatal mortality (36%). As against this, for less empowered women, access to maternal services (72 %) is low, lesser use of contraception (44%) and relatively higher neonatal mortality (43%). A systematic analysis of 175 countries (Lancet, 2010) has established that increase in women education decreases under five child mortality. Conclusions: Investments in women’s employment, health and education, are correlated with a range of positive outcomes, including greater economic growth and children’s health and survival.